POLA ASUH ORANG TUA DALAM PENGGUNAAN SMARTPHONE PADA ANAK USIA DINI DI KELURAHAN ELA-ELA KECAMATAN UJUNG BULU KABUPATEN BULUKUMBA - Halimah, Andi; Ramadani, Ainunniza Fitri; Rahman, Ulfiani; M. Yusuf; Nuryamin (JURNAL SIPAKALEBBI, 2024)
Smartphone use in early childhood has become an increasingly common phenomenon in modern society. Parents have an important role in guiding children in the use of this technology. The parenting style applied by parents can influence how children use smartphones and its impact on their development. This research aims to identify parenting patterns in the use of smartphones in early childhood in Ela-ela Village, Ujung Bulu District, Bulukumba Regency. This research is qualitative research with a phenomenological approach. Data collection techniques involve observation, interviews, and documentation. Furthermore, data processing and analysis techniques involve stages in the form of data reduction, data presentation, data verification, and drawing conclusions. The research results show that there are three types of parenting patterns that are commonly applied by parents, namely authoritarian, democratic and permissive parenting patterns. These results have implications for smartphone use in early childhood, where the parenting style chosen by parents can influence how children use smartphones. Therefore, understanding various parenting styles and their impact on child development is important for parents in educating and guiding their children.